Kegiatan Skrining Kesehatan dan Edukasi Penyakit Tidak Menular di Desa Kluwut Kabupaten Brebes - Seventina Nurul Hidayah; Nora Rahmanindar; Evi Zulfiana; Juhrotun Nisa; Umriaty Umriaty; Istiqomah Dwi Andari (Universitas Maritim AMNI Semarang, 2024)
Non-Communicable Diseases (NCDs) are diseases that cannot be transmitted from one individual to another, but depend on the individual's lifestyle. This shows that currently, non-communicable diseases are very important to be aware of, detected early, and prevented from getting worse and causing various complications and even death. About 80 percent of these deaths occur in middle- and low-income countries. 73% of deaths are currently caused by non-communicable diseases, 35% of them due to heart and blood vessel diseases, 12% due to cancer, 6% due to chronic respiratory diseases, 6% due to diabetes, and 15% due to other NCDs. The aim of the service is to provide education and health checks for PTM. The methods used in this community service are screening and education about non-communicable diseases. The potential result of this community service activity is an increase in community participation in PTM. It is hoped that this activity can be the first step in collaboration between community health centers, educational institutions and village officials in preventive efforts to prevent non-communicable diseases.